2019
DOI: 10.1016/j.jpurol.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sacral nerve stimulator explanation due to complications or cure: a survival analysis

Abstract: ConclusionSacral neuromodulation is a safe, viable option for the pediatric patient with refractory bladder dysfunction. Furthermore, SNM explantation for cure is an option with increasing likelihood after 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our study reinforces the expectations raised by Rensing et al, who demonstrated the possibility of discontinuing SNM under certain conditions in pediatric patients (median age at implantation of SNM was 10.1 years), as a possible strategy for the cure. In particular, in children with at least 2 years of SNM use and good treatment response, they showed that the chance of long-term successful removal of SNM is directly proportional to its duration of use ( 24 ). Our case shows this possibility also in the adult population as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reinforces the expectations raised by Rensing et al, who demonstrated the possibility of discontinuing SNM under certain conditions in pediatric patients (median age at implantation of SNM was 10.1 years), as a possible strategy for the cure. In particular, in children with at least 2 years of SNM use and good treatment response, they showed that the chance of long-term successful removal of SNM is directly proportional to its duration of use ( 24 ). Our case shows this possibility also in the adult population as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, implantable sacral neuromodulation involves placing an implantable pulse generator, electrodes, and a battery. In children, this procedure requires administering general anesthesia twice, and if the treatment is ineffective, a third procedure may be necessary for device explantation ( 5 ). Transcutaneous sacral nerve stimulation is a corollary treatment that does not need general anesthesia or an implantable device ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 This treatment also appears to be time limited as device explanation for cure occurs with increasing likelihood after 2 years. 10 There is currently a multi-institutional study ongoing (Sacral Neuromodulation Alliance for Pediatric Patients) to further evaluate this modality.…”
mentioning
confidence: 99%